Auditory anatomy of beaked whales and other odontocetes: Potential for cochlear stimulation via a "vibroacoustic duct mechanism" - March, D.; Brown, Daniel; Gray, R.; Curthoys, I.; Wong, C.; Higgins, D. (Wiley-Blackwell Publishing, 2016)
Computed tomography (CT) and microcomputed tomography (microCT) were used to examine the structures involved in cochlear stimulation in odontocetes and terrestrial mammals. Cranial CT examined the osseous attachment of the skull to the tympanoperiotic complex (TPC) and the path of the endocranial foramen of the vestibulocochlear nerve (EFVN), which was assumed to contain the perilymphatic duct. Additional CTs of TPC were taken postextraction to examine the gross morphology of this structure. MicroCT was used to examine the acoustic windows of the cochlea, including the round and oval windows and the apertures of the cochlear and vestibular aqueducts. Cranial CT scans demonstrated an osseous connection between the skull and TPC in beaked whales and Physeter macrocephalus. EFVN traveled through a greater length of cranial bone and communicated more closely with the periotic bone in beaked whales than in other species. Ziphius cavirostris was observed to have a reduced medial sulcus of the mallear ridge (MSMR) and tympanic plate and an enlarged aperture of the cochlear aqueduct, respectively. The potential significance of these findings, including the role of the perilymphatic duct as a novel route of cochlear stimulation referred to as the "vibroacoustic duct mechanism," are discussed.